2007
DOI: 10.1097/bot.0b013e31815a7e91
|View full text |Cite
|
Sign up to set email alerts
|

Union of a Chronically Infected Internally Stabilized Segmental Defect in the Rat Femur After Debridement and Application of rhBMP-2 and Systemic Antibiotic

Abstract: Recombinant human bone morphogenetic protein-2 maintained its osteoinductive capability in the presence of a chronic infection, and this property was enhanced by systemic antibiotic. This study presents an intervention that may potentially accelerate fracture healing in the presence of infection and colonized hardware, thereby permitting earlier removal of the hardware, and more timely and effective treatment of infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 19 publications
1
50
1
Order By: Relevance
“…These controls may have shown that no bone formation occurs in the absence of MDR AB. Bone formation has not been observed in this model of infection without some form of osteogenic treatment [3][4][5]. One explanation could be that the newly formed bone may be the result of the presence of the absorbable collagen sponge used to retain the bacteria in the defect in the short term.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…These controls may have shown that no bone formation occurs in the absence of MDR AB. Bone formation has not been observed in this model of infection without some form of osteogenic treatment [3][4][5]. One explanation could be that the newly formed bone may be the result of the presence of the absorbable collagen sponge used to retain the bacteria in the defect in the short term.…”
Section: Discussionmentioning
confidence: 82%
“…Recovered P. aeruginosa at 2 and 3 weeks were larger than initial inocula. Moreover, 10 6 CFUs of P. aeruginosa combined with 10 3 and 10 4 CFUs of SA resulted in dyspnea and death in several animals. In addition to the surprising reduction in bacterial counts with MDR AB, no bony lysis was radiographically evident at Weeks 2, 4, and 8 using 10 8 CFU of tracheal and bone isolates of MDR AB ( Table 2).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…A power analysis based on a previous study was used to determine the number of animals [2]. Assuming a power level of 0.8 and p value of 0.05, six animals would be required to determine a 60% difference between infection and noninfection groups in terms of mechanical testing.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies of infected fracture models, callus tissue was observed in the infected fracture area under the supply of antibiotics [2,3,24]. The difference from these studies is that no antibiotics were used and no segmental defects were created.…”
Section: Discussionmentioning
confidence: 99%